Interactions between Controlled Atmospheres and Low Temperature Tolerance: A Review of Biochemical Mechanisms - Boardman, Leigh; Sørensen, Jesper G.; Johnson, Shelley A.; Terblanche, John S. (Frontiers in Physiology, 2011)
Controlled atmosphere treatments using carbon dioxide, oxygen and/or nitrogen, together with controlled temperature and humidity, form an important method for postharvest sterilization against insect-infested fruit. However, in insects, the cross tolerance and biochemical interactions between the various stresses of modified gas conditions and low temperature may either elicit or block standard stress responses which can potentiate (or limit) lethal low temperature exposure. Thus, the success of such treatments is sometimes erratic and does not always result in the desired pest mortality. This review focuses on the biochemical modes of action whereby controlled atmospheres affect insects low temperature tolerance, making them more (or occasionally, less) susceptible to cold sterilization. Insights into the integrated biochemical modes of action may be used together with the pests’ low temperature tolerance physiology to determine which treatments may be of value in postharvest sterilization.